PEMETAAN DAN STRATEGI PENINGKATAN KUALITAS LAYANAN JASA WISATA TAMAN AIR PANAS DARAJAT PASS GARUT - Fahmi Mulya Azis; Andri Ikhwana; Rina Kurniawati (Institut Teknologi Garut, 2013)
This research will be done in Wisata Taman Air Darajat Pass Garut (DP) by spreading questionnaire customers and an interview with the owner and manager staff Electoral Area. Questionnaire consists of 25 questions which represents 5 dimensional quality of service that is direct evidence (Tangibel), reliability (reliability), tanggap (responsiveness), guarantee (assurance), and empathy (empathy). The methods used in the course of research is the method servqual and importance Performance matrix (IPM) and tourism development approach with the draft strategy the increase tourism. From 75 respondents who said that get quality of service that there are 9 is already a good and 5 that they feel it is not yet satisfying, especially in reliability (reliability) of employees to customers who have a problem when he was in the DP Area. Based on the analysis of the draft strategy tourism development, a strategy to improve the quality service excellence as well as to create services that can be used is a strategy usability comparing with the concept that has been there tourism in garut and by adding facilities such as therapy, hot spa body, and public facilities such as money charger.